MST 562 - Stochastic Processes (October 2003) - PPSM, Pusat Pengajian Sains Matematik (2003)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic Year 2003/2004 October 2003 MST 562 STOCHASTIC PROCESSES Time: - 3 hours Please ensure that this exam paper consists of SIX [6] printed pages before you begin the exam. Answer all FIVE (5) questions.